Cosmid cloning of Rickettsia prowazekii antigens in Escherichia coli K-12. - Krause, D C (Infect Immun, 1985)
Rickettsia prowazekii DNA was partially digested with Sau3A or HindIII, ligated with the cosmid vector pHC79, packaged in vitro, and transduced into Escherichia coli HB101. Cosmid cloning of Sau3A-digested rickettsial DNA yielded 1,288 ampicillin-resistant colonies; 798 cosmid clones resulted with HindIII-digested rickettsial DNA. Chimeric cosmid DNA was extracted from the latter gene bank, digested to completion with HindIII, and compared by agarose gel electrophoresis with a HindIII digest of rickettsial genomic DNA. The two digestion profiles were quite similar in their overall banding patterns, indicating that the clone bank was significantly representative of the rickettsial genome. When both clone banks were screened for expression of rickettsial antigens by enzyme-linked immunosorbent assay with goat anti-R. prowazekii serum, ca. 20% of the clones reacted positively. Two clones were randomly selected for more detailed analysis. Each contained a large chimeric plasmid (40.2 and 38.1 kilobases) which apparently yielded smaller deletion derivatives (13.6 and 12.6 kilobases) when transformed into an E. coli minicell strain. Each recombinant plasmid directed the synthesis of new protein species not observed in control minicells. One of the clones produced a 51,000-dalton protein in minicells, which comigrated with a protein reactive with anti-R. prowazekii serum. This protein was not present in negative controls. When antibodies to this protein were incubated with a Western blot of rickettsial total protein, they bound to a 52,000-dalton polypeptide. Hence, the cloned rickettsial gene product in E. coli corresponds to a protein of similar size in R. prowazekii. This study demonstrates the feasibility of cosmid cloning of rickettsial antigens in E. coli. IMAGES: